how to evaluate this integral: $$l(y)=\int\limits_\beta^\infty \theta\exp(-y\theta)\alpha\exp(-\alpha\theta) \, d\theta$$ where $\alpha,\beta,\theta,y>0.$ Because I find it infinity! Can anyone help me to evaluate this integral? Thank you.$$$$ I find this solution :$$\left(\left.\frac{-1}{(\alpha+y)^2}\exp(-(\alpha+y)\theta)\right)\right|_{\beta}^\infty-\left.\frac{\theta}{(\alpha+y)}\exp(-(\alpha+y)\theta)\right|_{\beta}^\infty.$$ $$$$ in which in the second term, I obtain infinity value!

  • $\begingroup$ Try substituting $t = exp(-\alpha \theta)$ . $\endgroup$ – Dilawar Nov 13 '12 at 8:14
  • 5
    $\begingroup$ Hint: Note that $\ell(y) = - \dfrac{\partial}{\partial y} \int_\beta^\infty \alpha \exp(-(y+\alpha) \theta)\ d\theta$ $\endgroup$ – Robert Israel Nov 13 '12 at 8:16
  • $\begingroup$ @Dilawar Or not. $\endgroup$ – Did Nov 13 '12 at 9:53

The product $$ \begin{align} x\exp(-x) &=x/\exp(x)\\ &=x/(1+x+x^2/2+x^3/6+\dots)\\ &=1/(1/x+1+x/2+x^2/6+\dots) \end{align} $$ $1/x\to0$ as $x\to\infty$ . Sum of other terms in the denominator $\to\infty$ as $x\to\infty$. So the product $x\exp(-x)\to0$ as $x\to\infty$.

  • $\begingroup$ It makes answers easier to read if you use MathJax. $\endgroup$ – robjohn Jan 16 '13 at 1:18

You're wrong, your 2nd term is not infinite ! Indeed exponential growth is much stronger than polynomial one, so $\lim_{x \to +\infty} x.e^{-x} = 0$.

Beware of the $\alpha$ factor inside the integral and signs, I found for my part: $$ l(y) = \left( \frac\alpha{(y + \alpha)^2} - \frac{\alpha \beta}{y + \alpha} \right) e^{-(y + \alpha) \beta} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.